Milk qualitative and quantitative characteristics, metabolic profile and rumen pH and NH3 concentration in grazing goats fed with two types of concentrate - Di Trana A.; Claps S.; Cifuni G.F.; Fedele V.; Impemba G.; Celi P. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
The aim of this study was to investigate the effect of two types of concentrates characterized by different degradation (starch and nitrogen rapidly degradable [PBC] and less rapidly degradable [PMB]) compared with the group not supplemented (P) on milk quantitative and qualitative (protein, fat, lactose, urea, saturated [SFA], monounsaturated [MUFA] and polyunsaturated [PUFA] fatty acids [FAs], CLA, C18:1t, ??-3, ?-6, thrombogenic index, atherogenic index) characteristics in lactating goats grazing on natural pasture. Goats were also monitored for rumen pH and ammonia (NH3) concentration and for their metabolic profile (NEFA, glucose, cholesterol, protein, urea, albumin and globulin). Concentrate supplementation increased milk yield in groups PBC, while in group P and PMB milk yield decreased, respectively 27% and 9%. Milk protein, fat, lactose and urea were not affected by the feeding regimen. CLA and C18:1 trans values increased by 47% and 39% in P and by 45% and 43% in PMB compared to PBC group, respectively. No differences in SFA, MUFA, PUFA fatty acids, ?-3, ?-6 FAs and thrombogenic index were found between PBC and PMB groups. The dietary treatments had a significant effect on the metabolic profile of the goats. Non-sterified fatty acids (NEFA) and cholesterol concentrations showed the highest level in group PBC. Group PMB presented the lowest NEFA and glucose concentration. Plasma urea levels were significantly higher in group P indicating an inefficient use of ruminal nitrogen. Total protein and globulin concentrations were higher in group PMB, while the maximum level of albumin was observed in group P. The maximum decrease in pH was found after two hours in PBC and after four hours in PMB. The ruminal NH3 concentration was the greatest for PBC at any time of ruminal fluid sampling. Results indicate that, under the grazing conditions, PMB dietary treatment improved milk quality, while milk yield was not significantly lower than PBC; also, in PMB group plasma metabolites showed better conditions of animals.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)